Paul and the ancient letter form - Porter, Stanley E., 1956-; Adams, Sean A. (Pauline Studies, 2010)
Throughout the last century, there has been continuous study of Paul as a writer of letters. Although this fact was acknowledged by previous generations of scholars, it was during the twentieth century that the study of ancient letter-writing practices came to the fore and began to be applied to the study of the letters of the New Testament. This volume seeks to advance the discussion of Paul's relationship to Greek epistolary traditions by evaluating the nature of ancient letters as well as the individual letter components. These features are evaluated alongside Paul's letters to better understand Paul's use and adaptations of these traditions in order to meet his communicative needs.